Professional Development of University Educators in Artificial Intelligence: Current State - R. Z. Elsakova; A. M. Markus’ (Высшее образование в России, 2024)
The rapid development of artificial intelligence (AI) has posed many dilemmas for higher education, one of which is the development of university educators’ competencies in using AI technologies in the educational process.   The purpose of this study is to present the current state of the problem of university educators’ professional development in the sphere of AI in the theory and practice of education.   To achieve the goal, theoretical and empirical methods were used. The group of theoretical ones includes the analysis of scientific literature and Internet sources, study and generalization of advanced pedagogical experience, comparative analysis, content analysis, systematization. The group of empirical methods includes document analysis, questionnaire and survey. The first part of the article presents the analysis of international and Russian regulatory documents, which showed the significance of the studied issue for the state and society, and also allowed us to find out that the legal framework regulating AI in higher education is currently undergoing the stage of active formation. The second part of the article presents the review of scientific publications by foreign and Russian scientists, which helped to highlight the theoretical aspects of the current state of the problem of university educators’ professional development in the field of AI, as well as to identify its insufficientcoverage. The third part of the article presents the results of the study of educational practice in the form of systematization of educators’ development programs offered by universities and commercial organizations at the moment. The systematization is made on two bases: by the means of implementation and by the target audience. The fourth part of the article describes the authors’ experience in the development and implementation of a professional development program for educators on the creation of educational content using neural networks which took place in South Ural State University (National Research University). The conclusion states the necessity of systematic study of the problem, coordination of actions of educational organizations and state bodies to develop a supporting regulatory framework, the necessity to create conditions that promote the continuous development of educators’ AI competencies.